SUPPORT OF STUDENT MANAGEMENT IN PROMOTING ACADEMIC ACHIEVEMENT: A CASE STUDY IN HIGHER EDUCATION - Kirani, Dinda; Marsofiyati (Faculty of Economics and Business, Universitas Negeri Jakarta, 2023)
This research aims to identify whether or not student management is present in promoting academic achievement in case studies in higher education. This research uses a quantitative method by collecting primary data through a questionnaire with a Likert Scale as an instrument distributed to active students. Then the respondents' answers that were obtained were processed using IBM SPSS 25 software. Based on testing the hypothesis in this research, the research results show that student management has a significant positive influence on student achievement at the Faculty of Economics, Jakarta State University. These findings show that universities that implement good student management tend to have higher learning achievement. This is indicated by the R Square value of 0.472. The results of this statistical calculation state that the ability of variable X (student management) to explain changes in variable Y (learning achievement) is 47.2%, the remaining 52.8% is explained by other variables. Furthermore, it can be proven from the T test results that student management has a value of 5.004 > t-table 1.701 with a Sig level. equal to 0.000 < 0.05, then Ha can be accepted and Ho is rejected.